2015
DOI: 10.4172/2161-069x.1000345
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Early Onset Colorectal Cancer in Arizona: A Comprehensive 15-Year Analysis of the Arizona Cancer Registry

Abstract: Introduction The aim of this study was to investigate and analyze the incidence of early-onset colorectal cancer in Arizona, using the Arizona Cancer Registry. Methods We performed a retrospective analysis of patients with colorectal cancer reported in the Arizona Cancer Registry from 1995-2010. Outcome measure: incidence of CRC in patients younger than 50 years. Results 39,623 cases of colorectal cancer were reported to the Arizona Cancer Registry during a period of 15 years. Overall, there was a 17% decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…However, our results are consistent with other Australian and international research (1117) showing a rising incidence of CRC in the AYA population over recent years. To date, trends in CRC incidence among Australian AYAs have only been explored to 2010 (17), with very limited other research examining colonoscopy use and costs and benefits in the younger population.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, our results are consistent with other Australian and international research (1117) showing a rising incidence of CRC in the AYA population over recent years. To date, trends in CRC incidence among Australian AYAs have only been explored to 2010 (17), with very limited other research examining colonoscopy use and costs and benefits in the younger population.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings show an increasing trend in CRC incidence in WA over 25 years; however, trends over the most recent decade could not be explored due to lack of post-2007 data as our analysis was based on an existing data source with end date of 2008. However, our results are consistent with other Australian and international research ( 11 17 ) showing a rising incidence of CRC in the AYA population over recent years. To date, trends in CRC incidence among Australian AYAs have only been explored to 2010 ( 17 ), with very limited other research examining colonoscopy use and costs and benefits in the younger population.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Two upregulated lncRNAs (HOTAIR and UCA1) and two downregulated lncRNAs (LOH12CR2 and PART1) were common between the microarray, CRN and circlncRNAnet results. Several studies have previously reported that HOTAIR is an oncogene that plays a crucial role in the progression of various types of cancer (20), including gastric cancer (21,22), lung cancer (23), colorectal cancer (24), liver cancer (25), gallbladder cancer (26), breast cancer (27), cervical cancer (28), ovarian cancer (29), and prostate cancer (30). The oncogene UCA1 is known to be involved in various types of cancer, such as gastric cancer (31), breast cancer (32), bladder cancer (33) and colorectal cancer (34).…”
Section: Discussionmentioning
confidence: 99%
“…Topical corticosteroids (TCS) are perhaps the most widely used agents amongst the therapeutic armamentarium and have been rightly acknowledged as a wonder drug in dermatological therapy (7). They provide immediate subjective and objective relief in symptoms in almost all inflammatory dermatoses thus justifying its rampant use.…”
Section: Introduction:-mentioning
confidence: 99%